On the Origin of cine-Substitution in the Stille Coupling of Trisubstituted Iodoalkene and trans-Vinylstannane - Kanoh, Naoki; Ohno, Yutaro; Itagaki, Tomohiro; Fukuda, Hayato; Iwabuchi, Yoshiharu (Synlett, 2013)
Factors determining the course of reaction (i.e., usual coupling vs. abnormal cine-substitution) in the Stille coupling of trisubstituted iodoalkene and trans-vinylstannane were investigated. The palladium-catalyzed reaction with triphenylarsine and lithium chloride in N-methylpyrrolidone gave the normal Stille coupling product in good yield and good selectivity, while the use of N,N-diisopropylethylamine and cuprous iodide in toluene afforded the cine-substituted product exclusively. It is proposed that transmetalation between vinylpalladium and vinylstannane species determines the course of reaction.
Keywords: Stille reaction; cross-coupling; palladium; regioselectivity; alkenes